2022
DOI: 10.3390/ma15134628
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fly Ash Inclusion and Alkali Activation on Physical, Mechanical, and Chemical Properties of Clay

Abstract: This study investigated the improvement in the behaviour of a clay soil due to the addition of alkali-activated fly ash as a stabilising agent, and the effects of different activation factors such as alkali dosages and silica moduli. The alkali activator solution used was a mixture of sodium silicate and sodium hydroxide. Class F fly ash was used as the precursor material for the geopolymerisation process. Soil samples stabilised with non-activated class F fly ash were prepared and tested to compare the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 58 publications
(141 reference statements)
0
7
0
Order By: Relevance
“…Table A4 (Appendix A) shows the UCS of fly ash-stabilized soils determined by many investigators and Figure 4 summarizes the mechanism of strength improvement in fine-grained soils stabilized with class C and class F fly ash based on the literature. It has been shown that the strength of soil stabilized with class C or class F fly ash shows an increase [3,10,16,27,33,35,88,98,101,[103][104][105][106][107][108][109][110][111][112][113][114]. However, several researchers have pointed out that there is an optimum level of fly ash addition to stabilize soil [51,60,104,115].…”
Section: Effects Of Fly Ash Inclusion On Unconfined Compressive Stren...mentioning
confidence: 99%
“…Table A4 (Appendix A) shows the UCS of fly ash-stabilized soils determined by many investigators and Figure 4 summarizes the mechanism of strength improvement in fine-grained soils stabilized with class C and class F fly ash based on the literature. It has been shown that the strength of soil stabilized with class C or class F fly ash shows an increase [3,10,16,27,33,35,88,98,101,[103][104][105][106][107][108][109][110][111][112][113][114]. However, several researchers have pointed out that there is an optimum level of fly ash addition to stabilize soil [51,60,104,115].…”
Section: Effects Of Fly Ash Inclusion On Unconfined Compressive Stren...mentioning
confidence: 99%
“…In some cases, a mix design can be so robust that comparably large variations of the precursor properties still provide satisfactory outputs; for example, in applications with minimal requirements such as earth embankments or substrate layers. [61][62][63] Key parts of the technical requirements also refer to safety during use and after the end of the product life cycle. This aspect is usually addressed by determining the leaching of heavy metals and selected organic compounds; the latter is usually not relevant to AAMs.…”
Section: What Are the Barriers?mentioning
confidence: 99%
“…Hence, performance consistency is a key concern when using waste‐based materials for alkali activation. In some cases, a mix design can be so robust that comparably large variations of the precursor properties still provide satisfactory outputs; for example, in applications with minimal requirements such as earth embankments or substrate layers 61–63 …”
Section: What Are the Barriers?mentioning
confidence: 99%
“…The samples were completely covered by platinum under a high vacuum environment during sample preparation. Moreover, the EDAX method was used to find the major elemental composition on the surface of treated particles [8,15,[20][21][22].…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…Pakir et al, [14] reported that the strength of clay soils increases with the increment of TX-85 content and curing period. As a result, this product can be categorized as a stabilizer agent [15].…”
Section: Introductionmentioning
confidence: 99%